2023
DOI: 10.1063/5.0137661
|View full text |Cite
|
Sign up to set email alerts
|

Scaling and lateral maneuverability of pitching foil in periodic freestream

Abstract: We formulate the thrust and lift coefficients using scaling laws to develop a guideline for the lateral maneuverability of a pitching foil in a periodic freestream. The scaling laws for thrust and lift coefficients of two-dimensional pitching foil in a periodic freestream are derived by considering added mass and circulatory forces. We examined the validity of scaling laws by conducting water tunnel experiments at a Reynolds number of 4.2 × 103. The key parameters are the pitch amplitude and phase difference b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The body’s oscillating motion was represented by the following equation for the computational model: In this study, a motion was performed in the x – y plane, and no motion in the z direction was assumed. As in the previous study [ 23 ], the body’s oscillating motion was simplified as the pitching motion shown in Equation (1). In this study, the computational model performed only rotational motion with the head coordinates fixed.…”
Section: Methodsmentioning
confidence: 99%
“…The body’s oscillating motion was represented by the following equation for the computational model: In this study, a motion was performed in the x – y plane, and no motion in the z direction was assumed. As in the previous study [ 23 ], the body’s oscillating motion was simplified as the pitching motion shown in Equation (1). In this study, the computational model performed only rotational motion with the head coordinates fixed.…”
Section: Methodsmentioning
confidence: 99%